Interplay of writing skill and inquiry–based learning strategy in EFL classroom - Sam Hermansyah; Andi Sadapotto (UAD TEFL International Conference)
The objective of the study is to improve the students’ writing skills through inquiry-based learning strategy of the first-year students of UMS Rappang. It employs collaborative classroom action research. The researcher and the collaborator teacher work together in designing the lesson plan, implementation, and reflection. Each cycle of the study comprises four meetings: three meetings for the treatment, one meeting for the writing test. The data were collected through observation checklists, writing tests, portfolios, field-notes, and the students’ writing performance. Inquiry-based learning takes five major steps. First, students answer the questions given by the teachers about a particular topic. Second, students observe the given pictures, objects, and reading texts, and share their ideas about the observation. Third, students take notes of the observation. Fourth, students discuss the results of the observation and do peer editing. Fifth, the students re-read their writing for content and clarity of meaning and produce the final version to be submitted to the teacher. During the process, the students are grouped heterogeneously, regardless of their achievement, so they can interact and help each other. The teacher controls and guides the learning activities.